### Present Remotely

Send the link below via email or IM

• Invited audience members will follow you as you navigate and present
• People invited to a presentation do not need a Prezi account
• This link expires 10 minutes after you close the presentation

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

No description
by

## Lari.Karol Sànchez

on 10 November 2012

Report abuse

#### Transcript of Interpretacion geometrica de derivada

La derivada primera f ' (a) es la pendiente de la recta tangente a la gráfica de la función f en el punto de abscisa "a". Propiedades de la derivada por definición El procedimiento en el ejercicio Derivada en un punto f(x) = x³ - 2x
PASO 1: Hallar f(x + h).
f(x + h) = (x + h)³ - 2(x + h)
f(x + h) = x³ + 3x²h + 3xh² + h³ - 2x - 2h
f(x + h) = x³ + 3x²h + x(3h² - 2) + (h³ - 2h)
PASO 2: Restarle f(x).
f(x + h) - f(x) = [ x³ + 3x²h + x(3h² - 2) + (h³ - 2h) ] - (x³ - 2x)
f(x + h) - f(x) = x³ + 3x²h + x(3h² - 2) + (h³ - 2h) - x³ + 2x
f(x + h) - f(x) = 3x²h + 3xh² - 2x + (h³ - 2h) + 2x
f(x + h) - f(x) = 3x²h + 3xh² + (h³ - 2h)
PASO 3: Dividir por h.
[ f(x + h) - f(x) ] / h = [ 3x²h + 3xh² + (h³ - 2h) ] / h
[ f(x + h) - f(x) ] / h = (3x²h / h) + (3xh² / h) + [ (h³ - 2h) / h ]
[ f(x + h) - f(x) ] / h = 3x² + 3xh + [ (h³ / h) - (2h / h)
[ f(x + h) - f(x) ] / h = 3x² + 3xh + (h² - 2)
PASO 4: Encontrar el límite cuando h -> 0.
. Lím . [ 3x² + 3xh + (h² - 2) ]
h -> 0
(Cambiamos todas las "h" por 0):
= 3x² + 3x(0) + (0² - 2)
= 3x² + 0 + (-2)
= 3x² - 2 Interpretacion geometrica de la derivada
Full transcript